Energy-efficient real-time deployment of mobile sensors in disaster-prone location. (2nd July 2019) - Nwadiugwu, Williams Paul; Kim, Dong-Seong; Lee, Jae-Min
Recent research works on real-time robot-assisted mobile sensor deployment have become rapid, as they tend to accomplish problem-solving tasks at both safe location and unsafe location. This paper proposes a technique to achieve a real-time energy-efficient deployment of mobile sensors in a disaster-prone location using a path-tracking algorithm. An enhanced path-tracking algorithm was introduced to be able to deploy mobile sensors in both presence and absence of obstacles. The simulation result investigates the real-time performances of the mobile sensor nodes deployment with respect to factors such as the minimal energy consumption of the nodes with neighbourhood sharing scheme, the end-to-end system threshold and the time variance for the deployed sensor nodes to reach the target location and back to the base station.